Dual Solutions Of Convection Boundary Layer Flows In Porous Media, Nanofluid And Viscous Fluid - Fauzi, Nur Fatihah (2018)
The dual solutions of the boundary layer flows and convective heat transfer equations can be obtained due to the nonlinearity of the differential equations and the difference of geometric or fluid mechanical parameters. Experimentally, the existence of dual or multiple solutions seem difficult to anticipate, thus mathematical computation is essential to provide the details of flow structure and to observe occurrence of dual or multiple solutions. This thesis presents a detailed numerical study on dual solutions for convection boundary layer problems by considering four different problem: (1) mixed convection flow of sphere through porous medium in presence of heat generation/ absorption at lower stagnation point; (2) magnetohydrodynamics (MHD) stagnation point flow over a stretching/shrinking sheet in a nanofluid with heat absorption and convective boundary condition; (3) mixed convection flow on a vertical flat surface with melting effect in a non-Darcian porous medium; (4) stagnation point flow and heat transfer over a nonlinear shrinking sheet with suction and slip effects.